REGULATORY ISSUES OF THE SMALL AGRICULTURAL FARMING DEVELOPMENT - E. Grishin (Вестник университета, 2018)
It is noted that the opportunities of the small-scale agricultural sector are not being used in full force. There are signicant diculties in starting and further developing small farming in lending, risk insurance, logistics, innovative modernization and especially in the segment of sales of products. The increment of scientic knowledge carries in itself the precise denition of small agrarian forms of farming, as well as the economic mechanism of the process of regulating the development of small-scale economic entities. Particular attention is paid to the procedure of independent and transparent receipt of subsidies for increasing the investment activity in the development of small forms of farming.